Evaluate the Effectiveness of an Information Booklet on Knowledge Regarding Learning Disabilities in Children among Primary School Teachers - Dr. Veena Ranaut; Haripriya Pathania (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Introduction: Learning Disabilities (LDs), also called Specific Learning Disabilities (SLDs), are neurodevelopmental conditions that emerge during a child's formal education. These disorders involve persistent and significant challenges in mastering basic academic skills. They are diagnosed when clear, measurable deficits exist in how the brain processes or interprets information, leading to inefficiencies in learning. The goal of the study was to evaluate the effectiveness of an information booklet on knowledge about learning disabilities in children among primary school teachers. Materials and Method: A pre-experimental study with a one-group pretest-post-test design was conducted to evaluate the effectiveness of an information booklet on knowledge about learning disabilities in children among primary school teachers. Using a non-random sampling, a total of 60 participants were selected through total enumeration sampling technique. Result: The Result findings revealed that 64.1% of participants had good knowledge, 34.4% had average knowledge, and 1.6% had poor knowledge regarding learning disabilities. The mean pre-test score was 21.28 (70.93%), indicating moderate baseline knowledge among primary school teachers. Following the intervention (information booklet), the post-test results showed a significant improvement: 90.6% of teachers demonstrated good knowledge, 9.4% had average knowledge, and none had poor knowledge. The mean post-test score increased to 24.64 (82.13%), reflecting a notable enhancement in awareness. Statistical analysis found no significant association between knowledge scores (pre-test or post-test) and demographic variables, including age, gender, education, teaching experience, school type, or prior training (*p* > 0.05). Conclusion: These findings confirm the information booklet’s effectiveness in enhancing teachers' awareness of learning disabilities, supporting its potential use in teacher training programs.
Keywords: Learning disabilities; teacher knowledge; educational intervention; pre-test–post-test